Hearing : A Physical Phenomenon - DANIEL, VANITHA; KUMAR, V.S. SURESH (SCHOOL SCIENCE, 2006)
EVEN IN THE quietest country side, there are still sounds, such as wind, singing birds and buzzing insects. Sound waves, a physical phenomenon, are sure to occur when a falling tree hits the ground. The human auditory system enables us to hear not only the sound produced by a falling tree, but also the birds singing in the trees and the wind blowing through their leaves. Our auditory systems are amazingly well adapted for detecting and interpreting an enormous variety of information.